MIFOLOGIYALÍQ OBRAZLARDÍŃ JANRLAR KESIMINDE TRANSFORMACIYASÍ - Kabilova, Gúlayım (ILIM hám JÁMIYET, 2026)
The artical scientifically and theoretically studies and discusses the transformation of myth into fairy tales, the ways in which mythological images are transformed from myth to fairy tales, and from fairy tales to epics. The typological nature of the mythological giant, the old woman with a beard, the fairy, and the dragon are illustrated with examples, and the extent to which these images change in fairy tales and epics.